2020
DOI: 10.1504/ijewm.2020.104367
|View full text |Cite
|
Sign up to set email alerts
|

Value stream mapping for sustainable change at a Swedish dairy farm

Abstract: This case study increases our understanding of Lean implementation in which value stream mapping (VSM) is used to create an action plan at a small dairy and cattle farm in southwest Sweden. The researchers, the farmer-owner, and farm employees followed a step-by-step approach that resulted in ideas for operational improvements for the dairy activity. Data were collected in interviews with the farmer/owner, researcher participation in workshops, and researcher observations. The results reveal that VSM is an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
0
13
0
4
Order By: Relevance
“…Few studies reported the concrete impact of lean practice implementation (Melin & Barth, 2020), except for the output projection of modelling-based research (Solano, Guisselle, Jairo, & Luis, 2020). Most research only evaluated the impacts based on case studies, action research, or perception-based impact evaluations with low generalisability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies reported the concrete impact of lean practice implementation (Melin & Barth, 2020), except for the output projection of modelling-based research (Solano, Guisselle, Jairo, & Luis, 2020). Most research only evaluated the impacts based on case studies, action research, or perception-based impact evaluations with low generalisability.…”
Section: Discussionmentioning
confidence: 99%
“…This section discusses a thematic analysis based on emerging topics in the literature. An analysis of lean tools and techniques in the collected literature shows the dominant use of VSM to reduce waste (Barth & Melin, 2018;de Steur et al, 2016;Folinas et al, 2014;Melin & Barth, 2020;Taylor, 2006;Vlachos, 2015). This tool allows visualisation of the overall and detailed process in organisations and supply chains.…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…VSM is adopted as a primary tool for implementing improvements by identifying operational wastes and oversees the material and information flow used to design the system (Rother and Shook, 2003). Efficacious applications of VSM in food supply chains have been reported in the literature with VSM used in enhancing operational performance of food processing industries in Ghana (Pokuaa-Duah and Nadarajah, 2020); tomato supply chain in Greece (Anastasiadis et al, 2020); dairy industry (Melin and Barth, 2020), Agri-food supply chain (Kumar and Kushwaha, 2015) etc.. Mapping is generally proceeded by the process of waste identification using Kaizens. Focusing on waste reductions and operation improvements (Kumar et al, 2018), Kaizens or continuous improvement have been accepted worldwide with its practical competency of combining waste elimination tools and techniques effectively (Melcher et al, 1990).…”
Section: The Lean Conceptmentioning
confidence: 99%